Eficacia de la actuación de los payasos sobre el miedo a procedimientos dolorosos en oncohematología pediátrica - Ortigosa Quiles, Juan Manuel; Riquelme Marín, Antonio; Álvarez Soto, Henar; Astillero Fuentes, María José; Sánchez Piñera, Inés (Psicooncología, 2017)
Objectives: To assess the effectiveness of the performance of a couple of hospital clowns on the fear response in patients in Oncohematology unit before applying a painful medical procedure (lumbar puncture or bone marrow aspiration). Patients and methods: 30 children aged 3-11 years-old (M = 6.93, SD = 2.78) underwent lumbar puncture or bone marrow aspirate in the ‘Virgen de la Arrixaca’ Hospital. The assessment consisted of the administration of: 5-Facial scale, the observation scale “modified Yale Preoperative Anxiety Scale” (m-YPAS), and physiological measures of pulse and mean blood pressure. Results: In the between-subjects-analysis, statistically significant differences in all measures, except for the scale of faces, after the performance of hospital clowns was obtained. After the hospital clowns left, groups were matched on their scores. In the within-subject analysis, significant differences between pretest and posttest were achieved in all measures for the control group. The effect size analysis indicates values on the Facial scale d = 0.22 (small effect size) and large effect size for pulse (d = 1.02), mean arterial pressure (d = 1.20), and the m-YPAS scale (d=0.99), before application of painful medical procedure. Conclusions: The presence of clowns helps to reduce the fear in the application of painful procedures. However, this effect is short-term, because after hospital clown leaves differences disappear between groups